Adolescent Mental Health and Dating in Young Adulthood. (November 2016) - Thorsen, Maggie L.; Pearce-Morris, Jennifer
Adolescence is a period of tremendous socioemotional change, when youth develop important relationship skills that they carry with them into adulthood. The mental health of individuals during this period might act as resources or impediments that impact their ability to cultivate such skills as well as outcomes in their later romantic relationships. The current study examines how multiple dimensions of adolescent mental health (depressive symptomology, self-esteem, mastery, and impulsivity) are associated with outcomes in romantic relationships across the transition to adulthood, such as relationship conflict, relationship happiness, and number of dating partners. Youth with higher mastery, self-esteem, and impulsivity during adolescence had more romantic dating partners across the transition to adulthood. High levels of depressive symptomology and low mastery during adolescence were also associated with greater conflict within dating relationships in young adulthood.